Pengaruh Fraud Hexagon terhadap Kecurangan Laporan Keuangan pada Perusahaan BUMN Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Maisyarah, Siti; Nelvirita, Nelvirita (Jurnal Eksplorasi Akuntansi, 2025)
This study examining the relationship between financial statement fraud and factors such as industry characteristics, auditor turnover, director turnover, the frequency of CEO pictures, and government programs is the overarching goal of this research. In order to test the hypothesis and look at how the variables were related, this study used quantitative approaches. Used information is secondary data collected from 2020–2023 annual reports of state-owned companies traded on the IDX in Indonesia. Over the course of four years, 96 observations were derived from this study's purposive sample strategy, which included 24 organizations. This study uses logistic regression. The research found that CEO photos reduce financial statement falsification. Industry traits, government activity, auditor turnover, director changes, and financial goals do not affect financial statement fraud.